1948
DOI: 10.1104/pp.23.4.425
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Potassium Deficiency and Excess Upon Certain Carbohydrate and Nitrogenous Constituents in Guayule

Abstract: The nature of the carbohydrates of translocation and the reserve carbohydrates in guayule has only recently been elucidated. McRARY and TRAUB (28) isolated a fructosan, tentatively identified as inulin, and HAS- SID et al. (19) definitely characterized this substance as inulin. Later, TRAUB and SLATTERY (41) showed that in addition to inulin, levulins are also present in guayule tissue, and in relatively greater amounts. TRAUB aid SLATTERY (41) also indicated the importance of relating the 89 per cent.ethan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0
1

Year Published

1949
1949
1971
1971

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 19 publications
1
9
0
1
Order By: Relevance
“…Hartt (21) attributed this response to increased amylase activity in potassium deficient plants. Cooil (9) reported that the observed increase was due to lack of condensation of soluble sugars into storage forms. Nightingale (38) felt that increased sugars were due to reduced protein synthesis.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Hartt (21) attributed this response to increased amylase activity in potassium deficient plants. Cooil (9) reported that the observed increase was due to lack of condensation of soluble sugars into storage forms. Nightingale (38) felt that increased sugars were due to reduced protein synthesis.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Numerous investigations have been conducted with established stands of alfalfa regarding the effect of defoliation on carbohydrate reserves and the role of reserves with respect to winter hardiness 2 (5,11). Little information is available about the accumulation of carbohydrates in alfalfa seedlings during early stages of development.…”
Section: Synopsis Substantial Concentrations Of Carbohydratesmentioning
confidence: 99%
“…Gregory andSen 1937, Hartt 1934). Accumulation of sugars, however, does not necessarily indicate retarded translocation, since it might be the result of disturbances in the equilibrium between sugars and their metabolic products (Sideris and Young 1945, Cooil and Slattery 1948, Evans and Sorger 1966.…”
Section: Introductionmentioning
confidence: 99%